Hubungan Pengetahuan Gizi Dan Asupan Energi,Protein Dengan Kejadian Kekurangan Energi Kronik Pada Remaja Putri Di SMA Negeri 1 Kupang Timur - Taosu, Kenny Peter; Setia, Agustina; Baumali, Alberth Matu Salak; Saleh, Asmulyati S (Kupang Journal of Food and Nutrition Research, 2025)
Chronic energy deficiency (CED) is a disorder that affects adolescent girls and can last for years, characterized by inadequate food intake, especially in terms of energy and protein. Adolescents who have good knowledge of nutrition will be able and willing to regulate their diet so that it is balanced, neither deficient nor excessive. This study aims to assess the relationship between nutritional knowledge, energy intake, and protein intake with the incidence of chronic energy deficiency (CED) among female students at SMA Negeri 1 Kupang Timur. This study involved 210 tenth-grade female students at SMA Negeri 1 Kupang Timur as the population. Of these, 68 female students were selected as samples using stratified random sampling. Data analysis was performed using the Chi-square test. The results of the study at SMA Negeri 1 Kupang Timur showed that nutritional knowledge was not significantly related to CEE status (p = 0.734). Similarly, energy intake (p = 1.000) and protein intake (p = 0.540) also did not show a significant relationship with KEK status. There was no significant relationship between nutritional knowledge and energy and protein intake with KEK status.